Differential diagnosis of Autism Spectrum Disorder (ASD) by CNV detection – can early diagnosis be improved? - Kwiatkowska, K. (2014)
Autism Spectum Disorder (ASD) is an impairment in neurodevelopment that can be recognized in the first years of life. Symptoms are diverse and vary in severity, determining prognosis and influencing the integration in the community. ASD is characterized by difficulties in interpersonal interaction, verbal and nonverbal communication, and by uncommon interests, inappropriate and uncontrolled behaviors, and repetitive activities. Specific and early diagnosis allows early and effective intervention that improves learning, communication and social skills of autistic children.